(NkONSTRUKTIWNAQ MATEMATI^ESKAQ LOGIKA S TO^KI ZRENIQ KLASSI^ESKOJ (B/s - (NnOWIKOW(B, (NpETR sERGEEWI^s; (NkABAKOW(B, (Na(B.(Nf(B.s ((NmOSKWA (B:s (NnAUKA(B. (NgL(B. (NRED(B. (NFIZ(B.-(NMAT(B. (NLIT(B.,s, 1977)
(NsPISOK LIT(B.: (NS(B. 318-320s
Keywords: (NmATEMATI^ESKAQ LOGIKAs